Investigation of the dynamics of the development of coherent structures of complex flow in jets and trails - Toleuov, G.; Isatayev, M.; Musataeva, A.; Akanserina, T.; Babasheva, D.; Rustemova, S.; Nurmagambetov, M.; Tamabek, D. (Recent Contributions to Physics, 2017)
The characteristic frequencies of the formation of vertical disturbances in natural development are investigated experimentally. Their dynamics has been studied using the phase averaging technique and is associated with visualized schemes of frequency fluxes of the disturbing force, which lead to significant changes in the average arithmetic and pulsation characteristics. A study of the structure of the vortex of a trails behind a cylinder of limited length shows that finite phenomena lead to destabilization of the Karman vortices and an extension of the circulation zone in the trail. More detailed information on the dynamics of the development of coherent structures can be obtained by using the phase averaging technique for converting flow velocity and temperature signals. For a more in-depth study of the relationship between the mixing processes and the dynamics of the development of coherent structures, this method and the method of synchronization visualization of the flash pulse in the investigated flow zone should be used. In this scientific work, an attempt has been made to explain the physical properties of the phenomena described above by in-depth study of coherent structures that are formed in the initial and transitional part of three-dimensional jets and trails behind the cylinders of finite length.